The Influence of Motivation on Alfamart Employee Performance - Aini Alkamalat; Berlin Musharafah Utami; Amelia Farah; Iriani Ismail (Pusat Riset dan Inovasi Nasional, 2025)
The company's success is influenced by employee performance, one of the main factors of which is work motivation. Motivation can come from intrinsic factors, such as job satisfaction and self development, as well as extrinsic factors, such as salary, incentives, and work environment. This study aims to analyze the effect of motivation on employee performance at Alfamart Perumnas Kamal with qualitative methods through in-depth interviews. The results showed that high motivation improves performance, while lack of appreciation, excessive workload, and poor communication lower morale. The main factors that drive motivation are career opportunities, job stability, and the reward system. Alfamart is advised to increase training, improve incentives, and strengthen internal communication to create a more conducive work environment, thereby increasing employee productivity and loyalty.